Primary Hyperparathyroidism: Modern Conception and Clinical Observation - L. M. Farkhutdinova (Архивъ внутренней медицины, 2020)
The article is devoted to one of the actual medical and social problems — primary hyperparathyroidism, the late diagnosis of which leads to the development of severe complications and an increased risk of premature death. Unlike developed countries, where 80% of cases are represented by mild forms of the disease, in the Russian Federation this indicator does not exceed 30%, while 70% are manifest forms. Widespread awareness of doctors of various specialties in the diagnosis of parathyroid adenoma is necessary for the timely detection of the disease. The article reflects the main stages of the study of the disease, the pathogenesis of the clinical manifestations of primary hyperparathyroidism, the classic symptoms of which are changes in the target organs of the parathyroid hormone — bone tissue, urinary system and gastrointestinal tract, is considered. Bone disorders are the most common manifestation of hyperparathyroidism and are characterized by increased bone metabolism with a progressive decrease in bone mineral density. Typical changes in the kidneys include nephrolithiasis and nephrocalcinosis, causing the formation of renal failure. Gastrointestinal signs of hyperparathyroidism are erosion and ulcers of the stomach and duodenum, prone to bleeding, recurrent pancreatitis. Diagnosis of the disease is based on laboratory results, characterized by elevated levels of calcium and parathyroid hormone in the blood. Visualization of the paradenomas in most cases is provided by ultrasound and scintigraphy. Removal of parathyroid adenoma is the most effective treatment. A clinical case of a severe form of the disease is presented, indicating an urgent need to take measures to solve the problem of primary hyperparathyroidism.